ANALYSIS OF PRODUCT QUALITY, DIGITAL MARKETING, BRAND IMAGE AND INNOVATION ON PURCHASE DECISIONS FOR SKINTIFIC COSMETIC PRODUCTS IN LHOKSEUMAWE CITY - Nurmafuzah; Mohd.Heikal; Ikramuddin; Muchsin (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of product quality, digital marketing, brand image, and innovation on purchasing decisions of Skintific cosmetic products in Lhokseumawe City. This study uses a quantitative method with data collection techniques through questionnaires distributed to 170 respondents who use Skintific products. The data analysis technique used is multiple linear regression with the help of the SPSS program. The results of the study indicate that the four independent variables, namely product quality, digital marketing, brand image, and innovation have a significant effect on purchasing decisions. Partially, product quality has a significance value of 0.004 with a positive coefficient of 0.229, digital marketing has a significance value of 0.008 with a coefficient of 0.255, brand image has a significance value of 0.003 with a coefficient of 0.186, and innovation has a significance value of 0.000 with a coefficient of 0.281. Thus, all proposed hypotheses are accepted. These findings indicate that improving product quality, effective digital marketing strategies, positive brand image, and continuous innovation can encourage consumers to purchase Skintific products.